Sweat gland adenocarcinoma with high serum levels of CA19-9 and CEA: difficulty in diagnosis and treatment - Park, Jungmyung; Go, Se-Il; Hee Kang, Myung; Lee, Won Sup; Lee, Min Jeong; Kim, Moon Jin; Kim, Hoon-Gu; Kim, Dong Chul; Lee, Jeong-Hee; Ko, Gyung Hyuck (European Journal of Oncology and Environmental Health, 2016)
Sweat gland adenocarcinoma is a rare form of adenocarcinoma of the skin. Its occurrence has been reported mainly on the scalp, upper extremities, or upper trunk. Even though it metastasizes to other major organs, we may not have difficulty in differentiating between primary lesions and metastatic lesions. Here, we will describe a 70-year-old Korean man with a diagnosis of adenocarcinoma accompanying high serum levels of CA 19-9 and CEA. PET-CT revealed multiple high glucose uptake lesions in the pancreas, lung, and submandibular gland. The final diagnosis was high grade eccrine ductal adenocarcinoma (type III) in sweat gland adenocarcinoma. The clinical course of this case was very aggressive in contrast to previously reported cases where sweat gland adenocarcinoma had a long indolent clinical course. This patient succumbed to disease progression 3 months after diagnosis.